2014
DOI: 10.3400/avd.cr.14-00080
|View full text |Cite
|
Sign up to set email alerts
|

Tracheo-Bronchial Obstruction and Esophageal Perforation after TEVAR for Thoracic Aortic Rupture

Abstract: A 67-year-old man was referred to our hospital for an ascending aortic aneurysm, thoracoabdominal aortic aneurysm and aortic regurgitation. Graft repair of the thoracic aortic arch and aortic valve replacement was given priority and completed, however he developed descending aortic rupture before the second scheduled surgery, and endovascular stent grafting was performed. He subsequently developed tracheobronchial obstruction and esophageal perforation. The patient underwent urgent esophagectomy and enterostom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 10 publications
0
11
0
Order By: Relevance
“…Watanabe et al [9] described a case of esophageal necrosis secondary to ruptured thoracic aortic aneurysm resulting in mediastinal hematoma causing compression of the esophagus. Several other case reports of esophageal necrosis have been described after thoracic endovascular aortic repair (TEVAR) due to mediastinal hematoma (Tobisch et al [10], Koizumi et al [11], Abou-Al-Shaar et al [12], Seto et al [13]). In contrast to these cases, in our case, there was no evidence of rupture of TAA or mediastinal hematoma.…”
Section: Discussionmentioning
confidence: 99%
“…Watanabe et al [9] described a case of esophageal necrosis secondary to ruptured thoracic aortic aneurysm resulting in mediastinal hematoma causing compression of the esophagus. Several other case reports of esophageal necrosis have been described after thoracic endovascular aortic repair (TEVAR) due to mediastinal hematoma (Tobisch et al [10], Koizumi et al [11], Abou-Al-Shaar et al [12], Seto et al [13]). In contrast to these cases, in our case, there was no evidence of rupture of TAA or mediastinal hematoma.…”
Section: Discussionmentioning
confidence: 99%
“…Delayed esophageal perforation secondary to thoracic aortic replacement or thoracic endovascular aortic repair (TEVAR) is a rare but potentially fatal condition [2, 47]. …”
Section: Discussionmentioning
confidence: 99%
“…Seto et al reported that although the exact mechanism of secondary esophageal perforation after stent grafting remains unknown, hypotheses include (1) direct erosion of the stent graft into the esophagus, (2) pressure necrosis caused by the self-expanding endoprosthesis, (3) ischemic esophageal necrosis due to disruption of the arteries that feed the esophagus, (4) infection of the stent-graft prosthesis (artificial graft for aortic replacement was included in our case), (5) pseudoaneurysm development, and (6) endoleakage into the residual aneurysmal sac [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…In such cases, the esophageal necrosis can be presented as either an aortoesophageal fistula [1][2][3] or a free esophageal perforation. [4][5][6][7] Both are extremely rare complications, and to the best of our knowledge, only 4 cases of free esophageal perforation following endovascular repair of thoracoabdominal aortic aneurysm (TAAA) have been described in the published literature, all with a fatal outcome. [4][5][6][7] Herein, we report the first case of successful management of a free esophageal perforation following emergency hybrid visceral debranching and distal endograft extension to repair a ruptured TAAA.…”
Section: Introductionmentioning
confidence: 99%